2021
DOI: 10.1021/acsinfecdis.1c00248
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Breath Metabolite Changes in Children with SARS-CoV-2 Infection

Abstract: SARS-CoV-2 infection is diagnosed through detection of specific viral nucleic acid or antigens from respiratory samples. These techniques are relatively expensive, slow, and susceptible to false-negative results. A rapid noninvasive method to detect infection would be highly advantageous. Compelling evidence from canine biosensors and studies of adults with COVID-19 suggests that infection reproducibly alters human volatile organic compound (VOC) profiles. To determine whether pediatric infection is associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 28 publications
0
69
1
1
Order By: Relevance
“…Six articles were included with a total of 4,093 participants. Patients’ recruited in the studies are individuals with suggestive symptoms of COVID-19 ( Wintjens et al, 2020 , Grassin-Delyle et al, 2021 , Ruszkiewicz et al, 2020 , de et al, 2021 ); acute respiratory distress syndrome (ARDS) patients requiring mechanical ventilation ( Grassin-Delyle et al, 2021 ); COVID-19 patients confirmed with RT-PCR ( Berna et al, 2021 , Shan et al, 2020 ), computed tomography (CT) and laboratory (antibody test) ( Shan et al, 2020 ). The study participants were then grouped into two based on their COVID-19 status (positive or negative).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six articles were included with a total of 4,093 participants. Patients’ recruited in the studies are individuals with suggestive symptoms of COVID-19 ( Wintjens et al, 2020 , Grassin-Delyle et al, 2021 , Ruszkiewicz et al, 2020 , de et al, 2021 ); acute respiratory distress syndrome (ARDS) patients requiring mechanical ventilation ( Grassin-Delyle et al, 2021 ); COVID-19 patients confirmed with RT-PCR ( Berna et al, 2021 , Shan et al, 2020 ), computed tomography (CT) and laboratory (antibody test) ( Shan et al, 2020 ). The study participants were then grouped into two based on their COVID-19 status (positive or negative).…”
Section: Resultsmentioning
confidence: 99%
“…Methods used to detect VOCs vary between studies, as summarized in Table 1 , with some already used patented breath analyzing devices. Three studies analyzed chemical constituents of exhaled breath using GC-MS breath analysis ( Berna et al, 2021 , Grassin-Delyle et al, 2021 , Ruszkiewicz et al, 2020 ). Three other studies made use of the electronic nose with a pattern recognition method ( Wintjens et al, 2020 , de et al, 2021 , Shan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations